Evaluation of Sales Promotional Tools of Mr. Breals Shawarma: Basis for Improving Promotional Program: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Mr. Breals Shawarma is a fast-food restaurant. The company was founded on July 29th of2021, during the pandemic, which allowed them to position the brand and increase sales.Mr. Breals Shawarma is a fast-food restaurant. The company was founded on July 29th,2021, during the pandemic, which allowed them to position the brand and increase sales.The findings of the study revealed that the majority of the respondents are 16-25 years old,female unemployed, and availed of price discounts. The respondents evaluated Mr. BrealsShawarma's sales promotion as “Effective.” The overall result obtained a weighted mean of3.05, interpreted as effective. As revealed, the problem encountered by the respondents is ithas limited visibility and display.The results revealed the following recommendation: use a variety of discounts, includingbundled discounts, customer loyalty discounts, volume discounts, and many others. Includemeans for acquiring the price reduction promotion, as well. Mr. Breals Shawarma shouldbegin creating a website to promote their free shipping promotion in order to reach morepeople and attract more customers. Include detailed instructions on how to take advantageof the free shipping promotion on the website or on a social media post to avoid misleadingclaims about the deal. Mr. Breals Shawarma should boost its buy-one-get-one offers bygiving additional products to customers, such as purchasing three get-one free drinks orother items, and so on, to improve its effectiveness and attract more clients. Mr. BrealsShawarma should start a sales campaign before and throughout the holiday to boost theimpact of the promotion.
Keywords: Business Administration